Political parties and Party Systems - WARE, Alan (Oxford University Press, 1999)
This is an introduction to the study of political parties and party systems. It Focuses primarily on liberal democracies and the approach is a comparative one. The book's aim is to explain to students of politics how and why parties and party systems differ from one country to another. However, it also seeks to provide a more detailed understanding of party politics in five particular countries.